Prevalence of early childhood caries in a selected district in Sri Lanka - F. N. Shahim; S. Abayaratna; S. Sivayogn; J. Perera (College of Community Physicians of Sri Lanka, 2004)
Introduction: Early childhood caries is a widely recognised health problem in many countries, even though it is a very much neglected problem in Sri Lanka.   Objective: The objective of this study was to determine the prevalence and severity of early childhood caries among chil11ren be low five years in the Kalutara district in Sri Lanka.   Methodology: This study was carried out using the latest diagnostic criteria developed by the National Institute of Dental Cranio- Facial Research, USA. A cross sectional descriptive design was adapted to determine the prevalence of early childhood caries.   A total of 830 children below five years participated in the study. A total of 20 clusters was selected by multistage stratified random sampling techniques. A cluster was a Public Health Midwife area, and a minimum of 40 children from each selected PHM area participated in the study.   All data collection was carried out by the Principal Investigator, asisted by a recorder. Clinical examination of the teeth of the children was carried out by the Principal Investigator.   Results: The prevalence of early childhood caries among children below five years was 63%. The prevalence rose sharply after one year from 23.3% to 76.l% during .the fifth year. The severity of the disease was found to be high, with the severe component of early childhood caries being high up to three years.   The mean dmft for children below five years was 4.65. A large proponion of the decay was untreated. A large proponion of caries was non-cavitated, thereby the need for caries arresting care is high.   Conclusions: Early Childhood Caries should be recognised as a priority health problem in Sri Lanka.